The Role of Cardiopulmonary Exercise Testing (CPET) in Pulmonary Rehabilitation (PR) of Chronic Obstructive Pulmonary Disease (COPD) Patients. (2nd November 2018) - Stringer, William; Marciniuk, Darcy
Abstract: Chronic obstructive pulmonary disease (COPD) is a common multisystem inflammatory disease with ramifications involving essentially all organ systems. Pulmonary rehabilitation is a comprehensive program designed to prevent and mitigate these disparate systemic effects and improve patient quality of life, functional status, and social functioning. Although initial patient assessment is a prominent component of any pulmonary rehabilitation (PR) program, cardiopulmonary exercise testing (CPET) is not regularly performed as a screening physiologic test prior to PR in COPD patients. Further, CPET is not often used to assess or document the improvement in exercise capacity related to completion of PR. In this review we will describe the classic physiologic abnormalities related to COPD on CPET parameters, the role of CPET in Risk Stratification/Safety prior to PR, the physiologic changes that occur in CPET parameters with PR, and the literature regarding the use of CPET to assess PR results. Finally, we will compare CPET to 6MW in COPD PR, the common minimal clinically important difference (MCID) is associated with CPET, and the potential future roles of CPET in PR and Research.